2021
DOI: 10.21203/rs.3.rs-772136/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Brewing and Probiotic Potential Activity of Wild Yeasts Hanseniaspora Uvarum PIT001, Pichia Kluyveri LAR001 and Candida Intermedia ORQ001

Abstract: Non-conventional yeasts can be isolated from a wide range of environmental sources, often found in beverage industry in mixed fermentations, in which the microorganisms’ inoculum usually is not fully known. It is important to know starter cultures, since in addition to favoring reproducibility, other properties can be discovered. Thus, the objective of this work was to identify and characterize yeasts isolated from environment, evaluating their probiotic potential and possible use in brewery. Isolates were obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
(7 reference statements)
0
2
0
Order By: Relevance
“…At concentrations lower than 2%, the response mechanism is a general one, while at higher concentrations, specific cellular response mechanisms are probably activated. Its ability to tolerate even 5% NaCl concentration is an important feature for members of this species, as previous studies have showed that H. uvarum has limited tolerance to saline stress [ 59 , 61 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At concentrations lower than 2%, the response mechanism is a general one, while at higher concentrations, specific cellular response mechanisms are probably activated. Its ability to tolerate even 5% NaCl concentration is an important feature for members of this species, as previous studies have showed that H. uvarum has limited tolerance to saline stress [ 59 , 61 ]…”
Section: Resultsmentioning
confidence: 99%
“…At lower values (pH 3.0), significant growth was only recorded in the isolates H. uvarum CMGB-M1 and P. kudriavzevii CMGB-M6. The tolerance of H. uvarum CMGB-M1 to highly acidic environments it is important since another study reported that low pH values inhibit growth of the members of this species [ 61 ]. In the case of P. kudriavzevii CMGB-M6, it is not surprising that this strain showed a high ability to grow at low pH values since members of this species are well-known as being highly tolerant to stress conditions.…”
Section: Resultsmentioning
confidence: 99%